Jogo e capitalismo de plataforma no sul global: um estudo do coletivo de criadores RPGLatam - Carneiro, Alexander Catunda (2023)
This work aims to explore and describe the phenomenon known as RPGLatam — a group of independent latin-american RPG creators —, relating it to the current economical and social context of platform capitalism. After a theoretical discussion on platform capitalism and its unfolding effects on society, labor, videogames and tabletop games, the research then turns itself to the description of the group. From an ethnographic approach, the participant observation technique is utilized alongside semi-structured interviews with members of the group and bibliographic references from specialized news websites, aiming to understand the inner workings of the group, its values and its practices. Knowledge about the group is contextualized through theoretical concepts about platform capitalism.